Conocimiento e impedimentos de metodos anticonceptivos: las mujeres del Centro de Salud en Cerro Verde, Cochambamba, Bolivia - King, Erin M., author; Yarrington, Douglas, author (Colorado State University. Libraries, 2004)
The purpose of this project was to measure the level of knowledge regarding contraception and family planning and the actual and potential impediments to women's ability to plan the number of children in their families. Methodology: The information was obtained through semi-structured interviews with NGO program directors, health center doctors, and the women who utilized the services of the Cerro Verde health center. Research conducted previous to the interviews provided a hypothesis, guided the structure of the interviews, and later supplemented the findings. Findings: There are several factors that influence women's access to and decision to use contraceptives: availability of information, presentation of the information, accessibility of contraceptives, economic situation of the family, and the opinion of the husband. Implications: Increasing the number of community programs, sponsored by the health centers and NGOs, aimed at both women and men, and teenaged girls and boys could potentially increase familiarity with methods of family planning, including contraception thereby expelling any misunderstandings or rumors about the effects of such methods.
Knowledge of and impediments to contraception: Cerro Verde, Cochabamba, Bolivia
Project includes a poster and a paper.
Keywords: Contraception -- Bolivia; Birth control -- Bolivia